The Chinese way from the traditional ideal of “Xiao Kang” to the modern development model - M. Y. Zakharov (Вестник университета, 2022)
The transformation of the traditional ideal of “Xiao Kang”, created in Ancient China, into the modern socio-economic development model with practical results has been analysed in the article. To this end, the specificity of the Confucian ideas of “Xiao Kang”, the long path of their restoration, cultivation, formalisation and transformation into clear guidelines for the strategic future of the country has been reviewed. The current theoretical provisions characterising “Xiao Kang” society, the Engel coefficient indicators used to measure the people’s living standard in contemporary China have been highlighted. Special attention in the article has been paid to understanding the role of “Xiao Kang” in shaping the Chinese development model, using this ideal image to show the advantages of Chinese goods in domestic and foreign markets, positioning the Chinese internationally and creating a sense of exclusivity and elitism in the Chinese nation.